Perspektif Hukum Tentang Penerapan Layanan Hak Tanggungan Elektronik - Sihite, Sri Rumada; Baharuddin, Wahdaniah (PATTIMURA Legal Journal, 2023)
Introduction: Electronic mortgage services issued by the ministry of agrarian and spatial planning in connection with the issuance of the 2019 Minister of Agrarian and Spatial Planning/Head of the Indonesian National Land Agency regulation regarding electronic mortgage services. Purposes of the Research: Is to look at the legal perspective regarding the implementation of electronic mortgage services in the Ministry of Agrarian Affairs and Spatial Planning. Methods of the Research: The type of research used is normative empirical research. The nature of this research is descriptive. Source of data used is secondary data. The nature of this research is descriptive analytical research and drawing conclusions using the deductive method. Results Originality of the Research: The research results show that the harmonization of the rules used in electronic mortgage services between conventional mortgage laws and the latest ministerial regulations is needed for improvement because there are several obstacles found by the authors based on observations in one of the land offices in North Sumatra